A Case Series of Adult-Onset Rasmussen’s Encephalitis: Diagnostic and Therapeutic Challenges - Castellano, James Francis; Meyer, Jenny A; Lado, Fred Alexander (Frontiers in Neurology, 2017)
Rasmussen’s Encephaahlitis is a rare neurologic disorder characterized by progressive gradual cerebral hemiatrophy and medically refractory epilepsy. The majority of the current literature on this topic is focused on the pediatric population. In this case series, we will review three cases of adult-onset Rasmussen’s encephalitis, as defined by fulfillment of the 2005 Bien criteria. The diagnostic challenge of characterizing this rare disease will be highlighted by the extensive serum, CSF, and pathologic sampling in all three patients. MR imaging and EEG data will be examined over time to characterize hallmark findings as well as progression. Additionally, we will review the various forms of therapy attempted in these three patients, namely anti-epileptic drug therapy and immunomodulatory therapy. This case series will highlight the presence of this uncommon neurodegenerative condition in adult populations by reviewing the diagnostic challenge, key clinical and pathologic findings, as well as therapeutic options and efficacy. We will also utilize this case series to critically evaluatexamine our cases in the broader context of atypical presentations of this disease and the value of current diagnostic criteria.